Ajustes de curvas de retenção de água para amostras indeformadas e deformadas em diferentes texturas de solo - Criado, Sara Victória Moreira de Siqueira (2018)
The objective of this work was to determine the water retention curve in the soil using the Richards pressure chamber, with undisturbed and deformed samples from three regions: Dourados, Itahumand Juti, belonging to different textural classes. and deformed in the 0 to 0.2 m layers. subjected to six pressures: 10-30 - 60 - 100 - 300 - 1500 kPa. The water retention curves in the soil estimated by the Richards chamber were adjusted by the Van Genuchtenequation, obtainingthecoefficientsθs, θr, α, m and n. The variables total porosity, macroporosity, microporosity, soil density and particle size were also measured. The evaluation of the retention curve based on the deformed samples demonstrates a contrary soil behavior when compared to the retention curve with the undeformed samples, since the amount of water slower than in the deformed samples when compared to the undisturbed samples at the first pressures, demonstrating a fragility of the soils when they are unstructured. Thisbehaviordemonstratestheimportanceofmaintainingthesoil structure for purposes and water, and the soul revolting, de-structuring of its original characteristic, results in a lower water retention, making irrigation management different than necessary.